2001
DOI: 10.1128/iai.69.3.1781-1794.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of WdPKS1 , a Gene Involved in Dihydroxynaphthalene Melanin Biosynthesis and Virulence in Wangiella ( Exophiala ) dermatitidis

Abstract: 1,8-Dihydroxynaphthalene (1,8-DHN) is a fungal polyketide that contributes to virulence when polymerized to 1,8-DHN melanin in the cell walls of Wangiella dermatitidis, an agent of phaeohyphomycosis in humans.To begin a genetic analysis of the initial synthetic steps leading to 1,8-DHN melanin biosynthesis, a 772-bp PCR product was amplified from genomic DNA using primers based on conserved regions of fungal polyketide synthases (Pks) known to produce the first cyclized 1,8-DHN-melanin pathway intermediate, 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
113
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 57 publications
2
113
0
4
Order By: Relevance
“…From these data, we conclude that pks-1 is, in part, responsible for melanin biosynthesis in C. globosum. The gene pks-1 encodes a polypeptide with 2181 amino acids which harbors five domains that are found in other fungal polyketide synthases ( Figure 1A), suggesting that melanin biosynthesis in C. globosum is accomplished via the DHN pathway defined in various fungi [22,47,48]. To confirm this, tricyclazole, an inhibitor of the DHN pathway, was added to plates.…”
Section: Discussionmentioning
confidence: 99%
“…From these data, we conclude that pks-1 is, in part, responsible for melanin biosynthesis in C. globosum. The gene pks-1 encodes a polypeptide with 2181 amino acids which harbors five domains that are found in other fungal polyketide synthases ( Figure 1A), suggesting that melanin biosynthesis in C. globosum is accomplished via the DHN pathway defined in various fungi [22,47,48]. To confirm this, tricyclazole, an inhibitor of the DHN pathway, was added to plates.…”
Section: Discussionmentioning
confidence: 99%
“…Although traditionally most associated with primary dermatotrophic forms of cutaneous and subcutaneous phaeohyphomycosis, this asexual fungus has recently become better known as a paradigm for this emerging mycosis because of its increasing detection as a systemic pathogen in both immunocompetent and immunocompromised patients (Matsumoto et al 1993(Matsumoto et al , 1994manipulated polymorphic vegetative nature, a well-characterized cell wall chemistry and a rapidly improving molecular tractability, it currently serves as the model of choice for discovering cell wall-related virulence determinants among the dematiaceous fungi, irrespective of the mycoses they cause and the morphotypes of the agents involved (Szaniszlo et al 1983;Montijin et al 1997;Kwon-Chung et al 1998;Szaniszlo 2002). The model studies have confirmed by molecular methods that both 1,8-dihydroxynaphthlene (1,8-DHN) melanin and chitin, a linear homopolymer of β(1 → 4) N-acetylglucosamine, have relevance to the virulence of W. dermatitidis, and therefore presumably the virulence of other dematiaceous pathogens of humans (Feng et al 2001;Wang et al 2001;Szaniszlo 2002;Liu et al 2004). They have also shown that chitin and β(1 → 3) glucan serve as the main structural constituents of the cell walls of W. dermatitidis and that chitin content varies widely with morphotype (Szaniszlo et al 1983;Montijin et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…6). The first class contains genes similar to DHN-melanin PKS genes of the fungi Exophila dermatitidis 61 , Colletotrichum lagenarium 62 and Alternaria alternata 63 . Sequence identity to numerous expressed sequence tag (EST) sequences from sexual and perithecial libraries suggest a role in melanin pigment synthesis during sexual development 64 .…”
Section: Polyketide Synthasesmentioning
confidence: 99%